A Set-Membership approach to short-term electric load forecasting - Jimena Diaz; Jose Vuelvas; Fredy Ruiz; Diego Patiño (Revista Iberoamericana de Automática e Informática Industrial RIAI, 2019)
This work presents a model for the short-term forecast of electric load, based on Set-Membership techniques. The model is formed by a periodic component and an adaptive non-linear autoregressive component. The identifications set of the non-linear model is increased at each estimation step.  The model is evaluated in a case study with more than 13.000 samples of hourly sampled energy demand, registered during three years at a rural town in Colombia. The performance of the estimator is evaluated and confronted to a linear autoregressive model and a standard Set-Membership model with fixed identification set. Results show that the proposed estimator is able to predict demand with an RMS error below 2.5% for validation data, using just a 5% of the available dataset for the model identification.